2021
DOI: 10.1186/s12910-021-00596-5
|View full text |Cite
|
Sign up to set email alerts
|

Prioritising ‘already-scarce’ intensive care unit resources in the midst of COVID-19: a call for regional triage committees in South Africa

Abstract: Background The worsening COVID-19 pandemic in South Africa poses multiple challenges for clinical decision making in the context of already-scarce ICU resources. Data from national government and the last published national audit of ICU resources indicate gross shortages. While the Critical Care Society of Southern Africa (CCSSA) guidelines provide a comprehensive guideline for triage in the face of overwhelmed ICU resources, such decisions present massive ethical and moral dilemmas for triage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 14 publications
4
23
0
1
Order By: Relevance
“…Burnout has been a major health care issue that has intensified with additional stressors arising from the COVID-19 pandemic. The findings are similar to existing literature which reported common knowledge that frontline health care workers had one of the highest incidences of burnout even before the pandemic [ 38 , 39 ]. Being at the frontline in direct contact with patients suspected or confirmed to have a COVID-19 infection exacerbates this.…”
Section: Discussionsupporting
confidence: 90%
“…Burnout has been a major health care issue that has intensified with additional stressors arising from the COVID-19 pandemic. The findings are similar to existing literature which reported common knowledge that frontline health care workers had one of the highest incidences of burnout even before the pandemic [ 38 , 39 ]. Being at the frontline in direct contact with patients suspected or confirmed to have a COVID-19 infection exacerbates this.…”
Section: Discussionsupporting
confidence: 90%
“…may contribute to feelings of loss of influence on work situation and burnout. Naidoo et al suggested increased use of triage committees to alleviate emotional burden 36 …”
Section: Discussionmentioning
confidence: 99%
“…Naidoo et al suggested increased use of triage committees to alleviate emotional burden. 36 Hospitals worldwide have had to increase their ICU capacity during the pandemic. However, there is a limit to how ICU capacity can be stretched, even if physical space in the hospital is available.…”
Section: Icu Capacity Expansionmentioning
confidence: 99%
“…As COVID-19 spreading rapidly exceeds hospital capacities, the decision between hospitalization or domiciliary management is crucial to relieve hospitals from overload [ 44 ]. Additionally, limited resource allocation poses a challenging issue in terms of clinical decision-making, in contexts where intensive care admission entails priority scores based on age, survival prognosis and pre-existing illnesses [ 45 ]. HHT is a rare disease potentially involving chronic conditions with a reduced life-expectancy, especially in absence of appropriate pre-emptive management [ 46 48 ].…”
Section: Discussionmentioning
confidence: 99%